Purificação de Links Virtuais para Mitigar a Degradação de Fidelidade em Redes Quânticas Multi-salto - Tavares, David; Abreu, Diego; Abelém, Antônio (Anais do Workshop de Redes Quânticas (WQuNets), 2026)
Successive entanglement swapping operations degrade end-to-end fidelity in multi-hop quantum networks. This work investigates a preliminary strategy that applies purification to intermediate virtual links under bit-flip noise. Comparing the baseline with a moderate-redundancy scenario, results show that virtual-link purification expands the feasible operating region of the network.